Influence of sudden incidents on the brand reputation of a firm and its reaction - Grüner, Ann-Kathrin (2017)
The automotive industry always has been crisis prone and with the most recent Volkswagen emission incident, this dissertation aims at understanding the effects of a crisis on the brand reputation of the affected firm, measured with 4 different frameworks (namely the RepTrak model, the Interbrand method, Young&Rubicam’s Brand Asset Valuator and Keller’s Customer-based Brand Equity), and its behaviors reacting to it during the course of the crisis. To provide a base for comparison, two case studies about Ford and Volkswagen were considered and contrasted. Examining the companies’ cases, it showed that both enterprises dealt rather similar with the incident faced, proving that the firms did not learn from prior similar incidents occurred to third parties. In determining the adequacy of the initiative actions compared to the theoretically suggested ones, it was found that neither company followed the suggestions made by existing literature and that the companies’ own actions proved rather inadequate, happening with delay, trying to hide the own misdeeds and eventually losing their customers’ trust. Deducing lessons learned for future crisis-affected enterprises, the two cases proved beneficial in confirming the essentiality of speed and timeliness in a crisis situation, the relevance of admitting oneself to the scandal before the media covers it, sincerity and consistency in one’s words and actions, equity in the treatment of affected parties and the importance of regarding the own situational context.